The Role of IMF Support in Crisis Prevention - Ramakrishnan, Uma (IMF Working Papers; Working Paper ;, 2006)
This paper examines the role of IMF-supported programs in crisis prevention; specifically, whether, conditional on an episode of intense market pressures, IMF financial support helps prevent a capital account crisis from developing and, if so, through what channels. In doing so, the paper distinguishes between the seal of approval inherent in IMF support and its financing, evaluates the interaction of IMF support with economic policies, and assesses whether IMF financing has a different impact on the likelihood of a crisis than other forms of liquidity. The main result is that IMF financing helps prevent crises through the liquidity provided (i.e., money matters). However, since the effect holds even after controlling for (gross) foreign exchange reserves, stronger policies and the seal of approval under an IMFsupported program must also play a role. Finally, the results suggest that IMF financing as a crisis prevention tool is most effective for an intermediate range of economic fundamentals.